Implementasi Pendidikan Agama Islam Berwawasan Lingkungan (Adiwiyata) Di Smp Negeri 2 Lamongan - Rokim Rokim (Universitas Islam Lamongan, 2023)
This research is motivated by the rampant environmental damage and the many natural disasters that can harm the ecosystem, this research is expected to form a generation that is aware and cares about environmental sustainability. This research is dIscussed about the implementation of environmentally sound Islamic religious education (Adiwiyata) at Lamongan 2 Public Middle School, and the inhibiting and supporting factors of environmentally sound Islamic religious education (Adiwiyata) at Lamongan 2 Public Middle School, this study uses a type of qualitative research, in which in this qualitative method the data collected comes from interviews, observation and documentation. The collected data were analyzed using descriptive analysis techniques. The results of this study are first, the implementation of environmentally sound Islamic religious education (Adiwiyata) at SMP Negeri 2 Lamongan with innovations made to adjust policies through the curriculum system, namely learning Islamic religious education integrated with learning environmental education (PLH), second through approaches students, abbreviated as